Predicting the three-dimensional grain structure of superalloys during vacuum arc remelting process - Xin Li; Tao Zhang; He Jiang; Jianxin Dong (Journal of Materials Research and Technology, 2023)
In order to study the influence of the vacuum arc remelting process (VAR) on the grain structure of the ingot and provide initial condition for the prediction and analysis of the subsequent process such as homogenization and billet forging, an efficient and accurate three-dimensional (3D) cellular automata method was developed for the VAR process, and all parts of the algorithm were rigorously verified, and it can be combined with the MeltFlow-VAR. An ingot of 718 alloy was smelted through experiment for calculation verification and proved the accuracy of the predictions. A new method for discretization of Euler angles to obtain orientation index is proposed and verified, which is more flexible and higher computationally efficient than previous algorithms. Aiming at the problem of a large number of cells and calculation time on large-scale VAR ingot in the future, a hybrid parallel scheme is designed, and it is expected to realize large-scale calculations on the supercomputer system. Finally, the effect of different cell sizes on the calculation results was also studied, and the grain size at the edge of the ingot was not affected by the cell size.